CARACTERIZAÇÃO DOS ELEMENTOS FÍSICOS DA BACIA DO CÓRREGO SANTO ANTÔNIO (RIO CLARO/SP) / Characterization of the physical elements from the Córrego Santo Antônio Basin (Rio Claro/SP) - Cenira Maria Lupinacci da Cunha; Débora Aparecida Machi (Sociedade & Natureza)
The objective of this research was to characterize the physical elements from the Córrego SantoAntônio basin, aiming to understand the influence of its surrounding areas towards theEdmundo Navarro de Andrade State Forest (ENASF). For this, we produced geomorphologicaland land use maps and compiled geological, soil and climatic data. Such influence wasevaluated in terms of the dynamics of the transportation of the materials from the stream sources,outside of ENASF and over agricultural areas. The physical characteristic analyzes indicatedthat this area is sensitive to the morphogenetic processes and that they were intensified andaccelerated by the land use surrounding the stream sources. Therefore, it is necessary to reevaluatethe land occupation and to fiscalize the accomplishment of the environmental lawsrelated to the land use in valleys.